Isoprostanes as physiological mediators of transition to newborn life: novel mechanisms regulating patency of the term and preterm ductus arteriosus - Chen, Jian-Xiong (2012)
BACKGROUND: Increased oxygen tension at birth regulates physiologic events that are essential to postnatal survival, but the accompanying oxidative stress may also generate isoprostanes. We hypothesized that isoprostanes regulate ductus arteriosus (DA) function during postnatal vascular transition. METHODS: Isoprostanes were measured by gas chromatography–mass spectrometry. DA tone was assessed by pressure myography. Gene expression was measured by quantitative PCR. RESULTS: Oxygen exposure was associated with increased 8-iso-prostaglandin (PG)F2α in newborn mouse lungs. Both 8-iso-PGE2 and 8-iso-PGF2α induced concentration-dependent constriction of the isolated term DA, which was reversed by the thromboxane A2 (TxA2) receptor antagonist SQ29548. SQ29548 pretreatment unmasked an isoprostane-induced DA dilation mediated by the EP4 PG receptor. Exposure of the preterm DA to 8-iso-PGE2 caused unexpected DA relaxation that was reversed by EP4 antagonism. In contrast, exposure to 8-iso-PGF2α caused preterm DA constriction via TxA2 receptor activation. Further investigation revealed the predominance of the TxA2 receptor at term, whereas the EP4 receptor was expressed and functionally active from mid-gestation onward. CONCLUSION: This study identifies a novel physiological role for isoprostanes during postnatal vascular transition and provide evidence that oxidative stress may act on membrane lipids to produce vasoactive mediators that stimulate physiological DA closure at birth or induce pathological patency of the preterm DA.